VARIABILITAS MUSIM HUJAN DI KABUPATEN INDRAMAYU - Fierra Setyawan (Pusbindiklat - LIPI, 2010)
Indramayu District is located in northern part of West Java. It has two seasons, dry season and rainy season. In this research, wet and dry rainy season in Indramayu District was investigated by using Standardized Precipitation Index (SPI). And also by using wavelet power spectrum analysis was investigated some factors that influence rainy season in this area. It is found that monsoon circulation is a dominant circulation that causing dry season (March – November) and rainy season (December–February). In extreme condition, El Niño – Southern Oscillation (ENSO) contributes to variability of rainy season. Index Southern Oscillation (SOI) influences variability of rainy season. If negative SOI occurred, mostly part Indramayu District has drier rainy season and the opposite, the rainy season will be wetter if positive SOI occurred. Another phenomenon that influences to the variability of rainy season is Indian Ocean Dipole (Dipole Mode Index, DMI). Negative DMI brings more precipitation. On the other hand, positive DMI influences to less precipitation.